Ensino de História frente à pandemia: desafios e perspectivas no município de Altamira-Pará - SANTOS, Thalia Karolayne Pereira dos (2023)
The present work aims to analyze and understand how history teaching is happening in the city of Altamira, Pará, identifying and highlighting the challenges faced by history teachers of the public school system (final years) during the pandemic caused by the coronavirus (Sars-CoV-2). Through this research, I intend to demonstrate the main difficulties and how teachers have been adapting to the new forms of online teaching. For this, it was necessary to investigate how the pandemic affected history teaching in the city; and to identify the difficulties caused by remote teaching, as well as to analyze how history teaching is developing in Altamira, in the state of Pará. In this sense, this is a qualitative research with a bibliographical approach, which is used to compose the theoretical basis from the careful and systematic evaluation of books, periodicals, documents, texts, maps, photos, manuscripts, and even material available on the Internet, etc. In general, the research had its objective reached, which was to perceive the knowledge of teachers and collaborate to improve this knowledge, encourage students to reflect about the contents covered in the History component, and that there is diversification in the classes with the help of technology, enrich the knowledge not only with digital tools, but also transform them into cultural tools, and encourage interdisciplinarity in the school environment.